STRUKTUR DEMOGRAFI POPULASI Rhizophora apiculata DI KAWASAN PESISIR TIMUR KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Ahmadryadi_ahmadryadi Ahmadryadi_ahmadryadi; Efriyeldi_efriyeldi Efriyeldi_efriyeldi; Bintal_amin Bintal_amin (Berkala Perikanan Terubuk, 2018)
The existence of mangrove ecosystems strongly support the sustainability of ecosystems in coastal areas. Rhizophora apiculata is one of the most common mangrove species in Indragiri Hilir regency (Inhil). This study aims to collect mangrove ecosystem databases covering the ecological structure of R. apiculata on the east coast of Indragiri Hilir Regency. Mangrove sampling was done by using line transect at two locations namely Kuala Enok Industrial Estate located in Tanah Merah Subdistrict and mangrove conservation area located in Sungai Asam Village, Reteh Sub-district. The results showed that population density of R. apiculata for tree category in Kecamatan Tanah Merah was 722.2 ind/ha and Sungai Asam village of Reteh sub district was 1000.0 ind/ha. Whilst the density of seedling category in both areas have the same value that is equal to 777.8 ind/ha. Based on the results of Bhattacharya method analysis using software FISAT II version 1.2.2., demographic structure of R. apiculata population in two areas there is only one size group with average stem diameter ranged between 8.0 - 8.6 cm.